The Intertextuality in Modern Novel: a case study in its origins, manifestations, and Interpretation - Radhi Bkheet, Raed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This paper aims to examine the phenomenon of intertextuality in the modern Arabic novel. It discusses the origins of this phenomenon and its various manifestations in Arabic narrative texts. The study also explores the influence of intertextuality on narrative structure and novelistic style, as well as its impact on language and linguistic expression. Furthermore, the paper investigates how intertextuality engages with characters and narrative patterns, shaping both the form and content of the text. It also considers the effect of intertextuality on the reader’s interpretation and its role in contemporary literary criticism. The study highlights the significance of Arabic literary heritage and its connection to modern texts, showing how intertextual references contribute to a renewed understanding of Arab identity. Through this analysis, intertextuality is presented as a creative and dynamic tool that helps reconfigure Arabic literary identity. Ultimately, studying this phenomenon enables both readers and critics to gain deeper insights into modern Arabic literature. The paper focuses on critical approaches and textual analyses that emphasize literary metaphors and cultural intersections in contemporary Arabic novels.